2022
DOI: 10.1186/s12865-022-00506-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of probiotics on immunogenicity of spermatozoa in couples suffering from recurrent spontaneous abortion

Abstract: Background Impaired spermatozoa immunogenicity can result in pregnancy complications such as recurrent spontaneous abortion (RSA). Given that spermatozoa contact with microbiota, it is possible that inappropriate microbiota composition in the reproductive tract could result in the alteration of spermatozoa antigenicity. Probiotics, as a representative of microbiota, may therefore have a beneficial effect on this altered immunogenicity. The objective of this study was to determine the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Studies have also shown that supplementation with Lactobacillus reuteri can improve sperm motility ( Valcarce et al, 2017 ) and increase testosterone levels in aged male mice ( Poutahidis et al, 2014 ). Supplementation with L. casei rhamnosus Döderleini improves sperm immunogenicity and might be helpful for couples suffering from recurrent immunological spontaneous abortion ( Rafiee et al, 2022 ). Oral administration of the three commensal Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that supplementation with Lactobacillus reuteri can improve sperm motility ( Valcarce et al, 2017 ) and increase testosterone levels in aged male mice ( Poutahidis et al, 2014 ). Supplementation with L. casei rhamnosus Döderleini improves sperm immunogenicity and might be helpful for couples suffering from recurrent immunological spontaneous abortion ( Rafiee et al, 2022 ). Oral administration of the three commensal Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that supplementation with Lactobacillus reuteri can improve sperm motility [58] and increase testosterone levels in aged male mice [74]. Supplementation with L. casei rhamnosus Döderleini improves sperm immunogenicity and might be helpful for couples suffering from recurrent immunological spontaneous abortion [75]. Oral administration of the three commensal Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%